2003
DOI: 10.1111/j.1527-5299.2003.01461.x
|View full text |Cite
|
Sign up to set email alerts
|

Heart Failure Disease Management: Impact on Hospital Care, Length of Stay, and Reimbursement

Abstract: Congestive heart failure (CHF) is a major medical problem with significant hospital costs. The authors developed an inpatient disease management program for CHF in a community hospital setting to determine if it is possible to: 1) increase implementation of Agency for Health Care Policy and Research criteria for CHF; 2) improve the quality of patient care, while lowering length of stay and treatment cost for CHF; and 3) maintain nursing staff satisfaction. The program encompassed a clinical pathway incorporati… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
12
1
2

Year Published

2005
2005
2019
2019

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 31 publications
(15 citation statements)
references
References 37 publications
0
12
1
2
Order By: Relevance
“…Among 46 studies identified, only 7 publications met the study inclusion criteria [5,10,22,23,28-30] and they were included in the systematic review for a total sample of 3,690 patients, as shown in Figure 1. This systematic review consists of three randomised controlled trials [11,22,23] one interrupted time series [5] and three controlled studies [28-30]. …”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…Among 46 studies identified, only 7 publications met the study inclusion criteria [5,10,22,23,28-30] and they were included in the systematic review for a total sample of 3,690 patients, as shown in Figure 1. This systematic review consists of three randomised controlled trials [11,22,23] one interrupted time series [5] and three controlled studies [28-30]. …”
Section: Resultsmentioning
confidence: 99%
“…Examining the effect of CPs on the length of stay, out of five studies [5,10,28-30] three studies showed a significantly shorter LOS in the care pathway group [5,28,30]. The overall results of the random-effects model showed that care pathway provided a positive reduction in LOS when compared with the standard care (WMD  = − 1.89, 95%CI  =  (−2.44-(−)1.33 days, P  < 0.001) (Figure 4).…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Numerous studies of HF DM programs have demonstrated improvements including decreased hospitalizations, improved prescribing patterns (improved use and dose of betablockers and ACE-I), decreased costs, and shorter lengths of stay. [9][10][11] Certain HF DM programs have enhanced their interventions by incorporating remote physiological monitoring (RPM). Studies citing use of remote monitoring yield ambiguous results; some have reported improved outcomes such as reduced mortality, decreased utilization, and lower hospital charges, [12][13][14] while others have found no differences when the RPM component is taken into account.…”
Section: Introduction Imentioning
confidence: 99%
“…Nurse-or case manager-based CHF disease management programs have shown great promise but focus on controlling costs and reducing readmission rates as much as improving processes and outcomes. [11][12][13] Facility-or physician-based audit/feedback strategies have failed to improve quality indicators 14 and at best have modestly improved 30-day mortality rates. 15 In any case, CHF disease management programs are not commonly used among physician organizations.…”
mentioning
confidence: 99%